A pirâmide e seu volume - Andrade, Sandro Antonio Godeiro de (2013)
This study aims to present alternative didactic that facilitate and make possible the teacher, the student of mathematics and the student’s primary education, learning methods to justify and demonstrate the validity of the formula for the volume of the pyramid. It proceeds to approach these reasons and demonstrations within orders prospects for geometric, algebraic and ludic when calculating formula of volume of the pyramid. Therefore, in five chapters, we discuss the historical aspects and algebraic pyramid,a survey of teachers on how we approach the volume of the pyramid in the classroom. There are some of the main methods used to demonstrate the validity of the formula for the volume of the pyramid. Solid material was used as a tool to verify intuitive formula for the volume of the pyramid, and finally we have presented some problems involving the subject in this pyramid education.